Strategi Peningkatan Kinerja Guru Besar Di Perguruan Tinggi Negeri - Ramly, Amir Tengku; Maarif, Syamsul; Sukmawati, Anggraini (Jurnal Manajemen (Edisi Elektronik), 2018)
Human resources are the most important asset for an organization, including the IPB. A vision of IPB become World Classy University (WCU) and Research-Based University (RBU) requires quality human resources, especially lecturers and professors. Quality of human resources capable of aligning IPB with the best universities in Indonesia and the world is quality lecturers and professors are high performing. Good performance should be supported by a good performance management and appropriate strategies. This study aims to formulate alternative strategies that influence the performance professor. This research method uses the AHP model (Analytical Hierarchy Process) with soft were of Expert Choice as an approach to looking at the structure and priorities of strategic alternatives. The results showed that the strategy of priorities to be implemented through the strategic management of IPB is the development of self capacity in main priority to the education factor with indicators is the development of lecturing materials through the function and main role of head of the department (Kadep).